Avaliação da evaporação do solvente de sistemas adesivos contemporâneos - Werle, Stefanie Bressan (2012)
Objectives: The aim of this study was to evaluate the effect of air-drying time on degree of evaporation of solvent (DE), microtensile resin-dentin bond strength (μTBS) and degree of conversion (DC) of adhesive systems. Methods: Four two-steps etch-and-rinse (Adper Single Bond 2, XP Bond, Prime & Bond 2.1 and Opti Bond Solo) and one one-step self-etch (Adper Easy One) were tested. The DE was measured gravimetrically (n=6) after 3, 5, 10, 20, 30 and 60 seconds by air-drying. For μTBS flat dentin surfaces were obtained from fifty caries-free extracted molars (n=5). The adhesive systems were applied to dentin surfaces according to the manufacturer s instructions and subsequently air-drying for the time proposed by manufacturer (A) or for prolonged time (B), corresponding to maximum DE in the times evaluated. A composite resin was used for coronal build-up. After 24h water storage at 37ºC, the specimens were sectioned in x and y directions to obtain bonded sticks (0.9 mm2) which were immediately subjected to μTBS (1mm/min). The DC (n=3) was calculated by Fourier-transform infrared spectroscopy with attenuated total reflectance considering air-drying times A and B. The data of DE were statistically analyzed by ANOVA and Tukey´s test, μTBS and DC were analyzed by T-Test (α = 0.05). Results: The prolonged time (B) increased the DE for all materials compared to manufacturer´s times, however improved μTBS only for XP Bond and Adper Easy One. DC was not affected by evaluated air-drying times. There was no significant correlation between DC and μTBS. Conclusion: The evaporation of solvent from adhesive systems is affected by air-drying. The effect of air-drying time seems be material-dependent on parameters evaluated. Changes in protocols of use may be necessary to obtain better properties.